Range Different of Mono-Energetic 290 MeV/u Carbon Ion Across Geant4 Version with Variation of I-values - Efendi, M. Arif; Yani, Sitti (Department of Physics Education, Universitas Mataram, 2024)
The mean ionization potential (I-value) is a primary determinant of the position of the heavy ion Bragg peak. To minimize their impact on beam range errors and quantify their uncertainties, the currently used I-values in Geant4 material database are revisited. The study aims at comparing set of I-values in different Geant4 versions and cross validation with PHITS Monte Carlo (MC) code. The Bragg curves of mono-energetic 290 MeV/u carbon ion beams in a Polymethyl Methacrylate (PMMA) phantom were simulated using Geant4 versions 10.6.2 and 11.2.1. Similar beam energies were replicated using the PHITS code. The Bragg curves showed good agreement between the two versions of Geant4 MC code for an I-value of 74 eV, corresponding to G4_PLEXIGLASS in the material database. When the I-value was lowered to 65 eV and 48 eV, the Bragg curves from Geant4 version 11.2.1 shifted to shallower depths. This research provides insights for evaluating the Geant4 physics model.